PENINGKATAN KOMPETENSI PEDAGOGIK GURU DENGAN PEMAHAMAN KONSEP DAN STRATEGI KURIKULUM MERDEKA - Thamrin, Muhammad Ilyas; Syarifuddin, Syarifuddin; Athirah, Putri (Arunika: Jurnal Pengabdian Masyarakat, 2023)
This workshop aims to help increase teacher competence in understanding concepts and strategies related to the independent curriculum. The activity involved 30 (thirty) teachers at SMPN 10 Bantimurung, Maros Regency and was held on 21-24 February 2022. There are topics that can be discussed in activities to increase teacher competence in the independent curriculum including: 1) The concept of the Independent Curriculum, 2) Learning Design, 3) Understanding of 21st Century Skills, 4) Project-Based Learning, 5) Use of Technology in Learning, 6) Evaluation of Learning